Proposed new interior design of Kebaya Fashion Retail for Mamilaya Collection at Lot 36723, (NO.80) Jalan Permaisuri Bainun (Jalan Kampar), Perak / Nor Hafiza Fadzir - Fadzir, Nor Hafiza (Faculty of Architecture, Planning and Surveying, 2011)
Basically this report is explain about all the assessment that been done along this final semester. Final student in Diploma Interior Design needs to come out with project report in order to gain knowledges about the whole final project in every aspects started from basic level to final presentatation. The title of my final project is Proposed New Design Scheme of Kebaya Fashion Retail for Mamilaya Collections at Lot 36723,(No.80) Jalan Permaisuri Bainun (Jalan Kampar) ,Perak. Kebaya is a tradition which is being followed by elder and teenagers. Every of the followers are intend to pay a visit to the retail. The client branch only at F-016 (Tingkat 1), Seasons Square Plaza, Jalan PJU 10/3C, Damansara Damai, 47830, Petaling Jaya, Selangor. The co-finder of the Mamilaya Collections is Encik Amirrudin Hassan are in the process of expanding their business. Ipoh is the best choice to proposed the new Kebaya Fashion Retail because there are no Mamilaya Collections’s branch there. Customer come to Mamilaya Collection retail is encreasing everyday, hence, this is the best opportunity to boost people came and grab the chance to have a visit at the branch. Moreover, we all know kebaya has promote on the runaway in our country and foreign country. Kebaya also usually use in the grand function.it is a tradition meanwhile. Therefore, kebaya is favoured by Malaysian because it is a part of Malaysian identity. It is important for all Malaysians to try a kebaya. This project is being proposed according to the projects goal and client requirement. The main objective is to design a retail with a suitable concept in order to give the customer a comfort visit to the kebaya retail. The process to complete this project is being held according to the design stage, starting with project brief, research and analysis, till lastly proposal design. In conclusion this proposal is the new design scheme which make the design process need to be research in every aspect require.